End-to-end efficiency quantification of an autonomous underwater vehicle propulsion system. (15th August 2021) - Lidtke, Artur K.; Linton, Nicholas P.; Wright, Hannah L.; Turnock, Stephen R.; Downes, Jon
Abstract: Increasing demand for versatile and long-endurance autonomous underwater vehicles puts significant design pressure on all aspects of AUV design and operation, including that of the propulsive system. The present study discusses testing of a thruster unit and several propellers developed to propel a hybrid glider/flight-style underwater vehicle. Due to the AUV being required to operate at largely different speeds and thrust levels between the two configurations, the propulsive subsystem needs to be capable of remaining efficient and effective across a wide range of operating conditions. Thus, the current results focus on quantifying all of the factors affecting the drive train, ranging from open-water performance of the propeller up to electro-mechanical efficiency of the magnetic coupling and geared electric motor. It is shown that, depending on the required operating point, total efficiency of the vehicle is primarily affected by non-linear low Reynolds number effects, sudden drop of gearbox efficiency at low revolutions and applied torques, as well as blade deformation, aside of the baseline propeller efficiency. Highlights: Multi-purpose thruster for a hybrid glider-AUV vehicle has been developed and tested. Low Re, blade bending, and gearbox efficiency have strong influence on performance Easily-swappable 3D printed propellers are robust and provide operational flexibility